Resonance Rayleigh Scattering, Second-Order Scattering and Frequency Doubling Scattering Methods for the Determination of Malachite Green in Aquatic Products - Zou, Yan; Geng, Weidong; Liu, Mousheng; Yang, Yaling (Asian Journal of Chemistry, 2011)
In presence of the HOAc-NaOAc buffer solution and heating condition, leucomalachite green (LMG) can reacts with I3– to form an ion-association complex. It made a significant enhancement of resonance Rayleigh scattering (RRS), second-order scattering (SOS) and frequency doubling scattering (FDS). The increments of scattering intensity (ΔI) were directly proportional to the concentration of leucomalachite green in a certain range. The detection limits were 1.2 ng mL-1 for resonance Rayleigh scattering method, 1.5 ng mL-1 for second-order scattering method and 1.5 ng mL-1 for frequency doubling scattering method, respectively. This result indicates that these methods exhibited high sensitivities. And they were simple and feasible. Three new highly sensitive and simple methods of determination leucomalachite green have been developed. With the reducing action of potassium borohydride, over 85 % of malachite green (MG) can be converted to leucomalachite green. So these can be applied to determine the malachite green in aquatic products.